Taurine inhibits serum deprivation-induced osteoblast apoptosis via the taurine transporter/ERK signaling pathway - Zhang,Lei-Yi (2011)
Taurine has positive effects on bone metabolism. However, the effects of taurine on osteoblast apoptosis in vitro have not been reported. The aim of this study was to investigate the activity of taurine on apoptosis of mouse osteoblastic MC3T3-E1 cells. The data showed that 1, 5, 10, or 20 mM taurine resulted in 16.7, 34.2, 66.9, or 63.75% reduction of MC3T3-E1 cell apoptosis induced by the serum deprivation (serum-free α-MEM), respectively. Taurine (1, 5, or 10 mM) also reduced cytochrome c release and inhibited activation of caspase-3 and -9, which were measured using fluorogenic substrates for caspase-3/caspase-9, in serum-deprived MC3T3-E1 cells. Furthermore, taurine (10 mM) induced extracellular signal-regulated kinase (ERK) phosphorylation in MC3T3-E1 cells. Knockdown of the taurine transporter (TAUT) or treatment with the ERK-specific inhibitor PD98059 (10 μM) blocked the activation of ERK induced by taurine (10 mM) and abolished the anti-apoptotic effect of taurine (10 mM) in MC3T3-E1 cells. The present results demonstrate for the first time that taurine inhibits serum deprivation-induced osteoblast apoptosis via the TAUT/ERK signaling pathway.